Chloroquine and hydroxychloroquine for COVID-19 treatment - Dwi Aris Agung Nugrahaningsih; Eko Purnomo (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2020)
Coronavirus disease 2019 (COVID-19) is an emerging disease caused bysevere acute respiratory syndrome coronavirus-2 (SARS-CoV-2) that has been causing many people around the world affected. There is no approved treatment for COVID-19. Meanwhile, vaccine development still needs a long time before it becomes available to protect people from contracting COVID-19. Repurposing the available drugs is one of the fastest ways to get COVID-19 treatment. Studies have been conducted to discover for COVID-19 treatment that results in the finding of potential medication for COVID-19. Chloroquine and hydroxychloroquine are some of the available medication that shows potential for COVID-19 treatment. Preclinical study showed that the both drugs are active against SARS-CoV-2 in vitro. A pilot clinical study also showed their efficacy in COVID-19 treatment. Many clinical trials are now being conducted to prove their safety and efficacy for the prevention and treatment of COVID-19. However, until now there are not enough data to support the use of these drugs in COVID-19 management. Under the pressure to treat COVID-19 patients with chloroquine or hydroxychloroquine, clinicians shouldnot use these drugs for COVID-19 without considering the available information regarding theiruse for COVID-19. This review summarized the evidence regarding the potential of chloroquine and hydroxychloroquine in COVID-19 management.